Analisa Pengaruh Standar Kerja Dan Kriteria Pegawai Terhadap Kinerja Pegawai Di Masa Pandemi Covid (Studi Pada Dinas Kepemudaan, Olah raga Dan Pariwisata Kota Malang) - Fauzi Imanudin; Hadi Sunaryo; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The high level of service in the current era of globalization requires every organization to be able to adjust and determine its strategy in dealing with changes that occur in order to improve services. In every process, every organization is inseparable from the human resources in it. Human Resources have a major role in all organizational activities. Without human resources, all organizational activities will not run well. What in the current covid-19 pandemic, the organization has all the Human Resources who are able to handle work at home. employees work to have more expertise in using technology because it does not support them to be in the office. The purpose of this study is to determine the description of work standards, employee criteria and employee performance, to analyze the effect of work standards and employee criteria on employee performance, to determine the effect of work standards on employee performance and to determine the effect of employee criteria on employee performance. The population and sample in this study were employees of the Department of Youth, Sports and Tourism of Malang City, amounting to 46 employees. Based on the data used, this research uses descriptive quantitative research methods. The sampling technique in this study is a saturated sampling technique. The analytical method used is multiple linear regression analysis using hypothesis testing by performing t test and F test. The results show that  Keywords: Work Standards, Employee Criteria and Employee Performance